2020
DOI: 10.5761/atcs.oa.19-00132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mitral Valve Repair versus Replacement for the Progression of Functional Tricuspid Regurgitation

Abstract: Background: Function tricuspid regurgitation (TR) is frequently observed in patients undergoing mitral valve surgery. It is unclear that mitral valve repair (MVr) or mitral valve replacement (MVR) has influence on the likelihood of late TR progression. Methods: This study included 193 patients with degenerative mitral valve disease who underwent either MVr or MVR. Detailed preoperative materials, follow-up information, and echocardiographic data were collected and statistically analyzed. Results: At 6 and 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…These indicators were then subject to multivariate analysis, where age, gender, LAD, AF, PH, and TRA are found to be independent risk factors affecting long-term S-FTR likelihood in MVR patients. Their correlation with S-FTR was supported by previous studies demonstrating close associations between LAD, PH, AF, and TRA with post-mitral valve surgery FTR [Gao 2020;Mutlak 2020;Choi 2018;Bertrand 2021], owing to long-term mitral valve diseases causing left atrial expansion, atrial muscle remodeling, plus AF-causing cardiomyocyte electrophysiological and mechanical changes [Beckhoff 2018]. Sustained AF, in turn, causes atrial mechanical activity loss, resulting in various pathological processes, including hemodynamic changes, further left atrial expansion, PH from vasoconstriction and remodeling, irreversible RV myocardial damage, and gradual TA increase.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These indicators were then subject to multivariate analysis, where age, gender, LAD, AF, PH, and TRA are found to be independent risk factors affecting long-term S-FTR likelihood in MVR patients. Their correlation with S-FTR was supported by previous studies demonstrating close associations between LAD, PH, AF, and TRA with post-mitral valve surgery FTR [Gao 2020;Mutlak 2020;Choi 2018;Bertrand 2021], owing to long-term mitral valve diseases causing left atrial expansion, atrial muscle remodeling, plus AF-causing cardiomyocyte electrophysiological and mechanical changes [Beckhoff 2018]. Sustained AF, in turn, causes atrial mechanical activity loss, resulting in various pathological processes, including hemodynamic changes, further left atrial expansion, PH from vasoconstriction and remodeling, irreversible RV myocardial damage, and gradual TA increase.…”
Section: Discussionsupporting
confidence: 75%
“…It is classified into primary and secondary types, where the former results from inherent valvular disease, while the latter does not involve any valvular abnormalities. Secondary, also known as functional TR (STR/FTR), is a common occurrence post mitral valve replacement (MVR) surgery of rheumatic heart disease (RHD), and often is aggravated post-operation, leading to irreversible RV dysfunction, heart failure, and death [Topolsky 2019;Gao 2020;Wang 2019]. As a result, the 2020 American Heart Association/American College of Cardiology guidelines recommend severe FTR (S-FTR) patients to simultaneously undergo MVR and tricuspid valve (TV) surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of MV surgery on the progression of TR is inconsistent in the literature. 26 Gao et al 27 found that MV replacement was an independent predictor of recurrent TR in patients with degenerative etiology. 27 Literature comparing the effect of mitral surgery on TR in different MV pathologies is limited.…”
Section: Discussionmentioning
confidence: 99%
“…26 Gao et al 27 found that MV replacement was an independent predictor of recurrent TR in patients with degenerative etiology. 27 Literature comparing the effect of mitral surgery on TR in different MV pathologies is limited. Our results could support the hypothesis that MV surgery did not affect TR progression in rheumatic and degenerative etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is reassuring to note that progression of untreated non-severe TR is far less common (<5%-10% of cases) than stability or regression after aortic or mitral valve surgery. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%